Ginsenoside CK Inhibits the Early Stage of Adipogenesis via the AMPK, MAPK, and AKT Signaling Pathways - Oh, Jung-Mi; Chun, Sungkun (Antioxidants, 2022)
Obesity is considered a health hazard in part due to the associated multiple diseases. As rates of obesity continue to increase, a new strategy for its prevention and treatment is required. Compound-K, an active ingredient in ginseng, possesses antioxidant, anti-inflammatory, and anti-cancer properties. Although ginseng has used as various therapeutics, its potential ability to alleviate metabolic diseases by regulating adipocyte differentiation is still unknown. In this study, we found that CK treatment significantly inhibited lipid droplet and adipogenesis by downregulating the mRNA expression of C/ebpα, Ppar-γ, Fabp4, Srebp1, and adiponectin as well as protein levels of C/EBPα, PPAR-γ, and FABP4. CK also decreased the production of reactive oxygen species (ROS), while it increased endogeneous antioxidant enzymes such as catalase, glutathione peroxidase (GPx), glutathione reductase (GR), superoxide dismutase (SOD) 3 and SOD2. We observed that CK treatment suppressed the expression of cyclin-dependent kinase 1 (CDK1) and cyclin B1 during the mitotic clonal expansion (MCE) of adipocyte differentiation, and it arrested adipocytes at the G2/M stage due to the increased expression of p21 and p27. CK decreased the phosphorylation of extracellular signal-regulated kinase (ERK) and p38 and protein kinase B (AKT) in early-stage adipogenesis. In addition, the inhibition of adipogenesis by CK significantly increased the phosphorylation of AMP-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC). Interestingly, AMPK pharmacological inhibition with Dorsomorphin limited the effect of CK on suppressing PPAR-γ expression in differentiated 3T3-L1 cells. Our results suggest that CK exerts anti-adipogenic effects in 3T3-L1 cells through the activation of AMPK and inhibition of ERK/p38 and AKT signaling pathways.